2017
DOI: 10.1097/sap.0000000000001055
|View full text |Cite
|
Sign up to set email alerts
|

Can We Preserve the Urethral Plate in Proximal Hypospadias Repair?

Abstract: The essential factor responsible of curvature associated with proximal hypopsadias is the fibrosis tissue present on the ventral side of the penis. However, in the severe forms, a short urethral plate must be transected to obtain a complete correction of the chordee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
20
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…The proximal forms of hypospadias represent approximately a third of cases of this urogenital malformation. These forms are very often associated with curvatures ( 2 ). Thus, the treatment of proximal hypospadias includes two surgical stages: correction of the curvature and urethroplasty.…”
mentioning
confidence: 99%
“…The proximal forms of hypospadias represent approximately a third of cases of this urogenital malformation. These forms are very often associated with curvatures ( 2 ). Thus, the treatment of proximal hypospadias includes two surgical stages: correction of the curvature and urethroplasty.…”
mentioning
confidence: 99%
“…We conducted a scientific study on a large number of patients to know the causes of curvature associated with proximal hypospadias; this study that lasted more than 20 years and whose results were published successively ( 1 , 5 , 6 ) clearly shows the essential factor responsible for the formation of the curvature associated with proximal hypospadias is the fibrosis tissue present on the ventral side of the penis. The release of the skin and dartos fascia continued widely upstream of the meatus gives a significant correction (ranging from 20 to 100°).…”
mentioning
confidence: 99%
“…However, the curvature of the penis is an anomaly very often present in the proximal forms of hypospadias. In a recent study (182 patients) ( 6 ), the saline erection test performed at the beginning of the operation showed that only 14% of patients had a curvature (≤45°), 54% (45–90°), and 31% (≥90°). This is completely different from the findings reported by Snodgrass and the authors who report “an absence or mild curvature (<30°) in 50% of patients with proximal shaft to perineal hypospadias” ( 7 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations